Penciptaan Karya Seni “Aku Bukan Aku” Intepretasi Fenomena People Pleaser dari Isu Psikologis Sosial yang Dialami Individu - Ova, Anggi Safandri; Syahril, Syahril; Ariastuti, Idun; Osmond, Dony (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work "Aku Bukan Aku" is inspired by a people pleaser phenomenon as a psychological and social issue that is often experienced by individuals, especially the younger generation, in their daily lives. People pleaser refers to a person's tendency to always prioritize the interests, feelings, and expectations of others over their own needs, in order to gain social acceptance, avoid conflict, and maintain the image as a "good" person. This attitude can slowly cause inner pressure, emotional exhaustion, loss of identity, and identity crisis. The phenomenon is then translated into works of art as a form of reflection and social criticism through the medium of body expression. The body is positioned as an experience space that records the psychological burden, excessive obedience, and inner conflict experienced by individual people pleaser.